Samoa : Assessment of Financial Sector Supervision and Regulation including Report on the Observance of Standards and Codes on Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2007)
This assessment of Financial Sector Supervision and Regulation for Samoa provides an overview of legal and institutional frameworks. Compliance with the Basel Core Principles (BCPs) for the supervision of international and domestic banks has improved considerably. Supervision of domestic banks should be strengthened further through issuance of additional guidance on banks' risk-taking activities and corporate governance. Consideration should be given to enhancing the operational independence of the Samoa International Finance Authority (SIFA) to supervise international banks.